Movement initiation and preparation in subjects with schizophrenia: the amplitude of the readiness potential as a biological marker for negative symptom severity - Vöckel, Jasper; Thiemann, Ulf; Weisbrod, Matthias; Schröder, Johannes; Resch, Franz; Klein, Christoph; Bender, Stephan (Schizophrenia research, 2023)
Objective - Despite extensive research, the etiology of negative symptoms is not well understood. Preliminary findings are linking motor disturbances to negative symptom severity. We aimed to further the understanding to what extent motor movement preparation influences negative symptom severity. - Methods - In a cohort of 31 subjects with schizophrenia and 20 control subjects we recorded the readiness potential amplitude over Cz during spontaneous movements of the right and left thumb. We further assessed negative and positive symptom severity (scale for the assessment of negative and positive symptoms) as well as neurological soft signs (NSS). - Results - In subjects with schizophrenia the severity of negative symptoms was best predicted by the readiness potential amplitude and the NSS subdomain motor coordination. The correlation between deficits in motor coordination and negative symptom severity was partially mediated by the readiness potential amplitude in subjects with schizophrenia. - Conclusions - Deficits in motor processing are linked to negative symptom severity in schizophrenia. The readiness potential may represent a biological marker of these basal deficits. In combination with the assessment of NSS, the readiness potential may be a marker of the course of negative symptom severity and help clarifying interdependencies between (pre)frontal networks for action initiation and coordination, as well as negative symptoms.
Online veröffentlicht: 3. August 2023
Gesehen am 11.10.2023